Role of miRNA-182 and miRNA-187 as potential biomarkers in prostate cancer and its correlation with the staging of prostate cancer - Nayak,Brusabhanu (2020)
ABSTRACT Purpose The microRNAs expression has emerged as a potential biomarker for the diagnosis and prognosis of prostate cancer. This study investigated the expression of miRNA-182 and miRNA-187 in prostate cancer patients and established a correlation between miRNA expression and staging of prostate cancer. Materials and Methods This prospective observational study involved patients undergoing transrectal ultrasound-guided biopsy for suspicion of prostate cancer. Pre-biopsy urine samples and prostatic core tissue samples of the patients were preserved and the miRNA-182 and miRNA-187 were studied. Results Sixty-three patients were included in this study, thirty-three patients were diagnosed with prostate cancer and thirty patients having benign histopathology were considered as controls. The expression of miRNA-182 was significantly increased (p=0.002) and miRNA-187 significantly decreased (p <0.001) in prostate cancer tissue specimens. However, the expression of these miRNAs did not significantly differ in the urine of prostate cancer patients as compared to controls. Serum Prostatic Specific Antigen (PSA) inversely correlated with the median expression of miR-187 in prostatic tissue (p=0.002). Further, the expression of miRNA-187 in prostate cancer tissue was significantly decreased in metastatic prostate cancer (p=0.037). Using ROC analysis, miRNA-187 expression was able to distinguish the presence or absence of bone metastasis [area under ROC (AUROC) (±SD) was 0.873±0.061, p <0.001]. Conclusion The miRNA-182 and miRNA-187 appear to be promising biomarkers in prostate cancer and miRNA-187 can serve as an important diagnostic marker of metastatic prostate cancer.